2018
DOI: 10.1002/jcb.27857
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐142 in the pathogenesis of osteosarcoma and its potential as therapeutic approach

Abstract: Osteosarcoma (OS) is the most common primary malignant tumor of the bone with a strong tendency to early metastasis, and occurs in growing bones more commonly in children and adolescents. Considering the limited therapeutic methods and lack of 100% success of these methods, developing innovative therapies with high efficacy and lower side effects is needed. Meanwhile, miRNAs and the studies indicating the involvement of miRNAs in OS development have attracted attentions as a result of the frequent abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 110 publications
(350 reference statements)
0
20
0
Order By: Relevance
“…Xu et al [ 41 ] reported that miR-142-3p was downregulated in osteosarcoma tissue and cell lines. Several target mRNAs of miR-142-3p have been proposed including HMGA1, HMGB1, and Rac1 [ 42 ]. In hepatocellular cancer, miR-142-3p was shown to bind the 3′-UTR region of HMGB1 and resulted in the inhibition of proliferation and invasion of tumor cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 41 ] reported that miR-142-3p was downregulated in osteosarcoma tissue and cell lines. Several target mRNAs of miR-142-3p have been proposed including HMGA1, HMGB1, and Rac1 [ 42 ]. In hepatocellular cancer, miR-142-3p was shown to bind the 3′-UTR region of HMGB1 and resulted in the inhibition of proliferation and invasion of tumor cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…[44] These results suggest that miR-145-3p may play a role as a tumor suppressor in OSs. [45,46] Circular RNAs(circRNAs) have a circular structure and represent a common class of the uncoded RNAs. Many circRNAs have been reported to play a significant role in cancer development and to have the potential to serve as a new bioindicator class for clinical diagnosis.…”
Section: Mirna Circrna and Lncrna In Osteosarcomamentioning
confidence: 99%
“…Studies have demonstrated the role of cir-cUBAP2 in the development of OS, and it plays a significant role in the prognosis prediction and cancer treatment. [45,47] Long noncoding RNAs (lncRNAs) are a subclass of a transcriptional RNA molecules longer than 200 nucleotides that function as the regulatory factors in various human disease. IncRNA-ATB may be a potential therapeutic target for OSs.…”
Section: Mirna Circrna and Lncrna In Osteosarcomamentioning
confidence: 99%
“…Osteosarcoma is one of the most common cancers that accounts for 60% of all sarcomas (Cormier & Pollock, ; Heare, Hensley, & Dell'Orfano, ). Occurs in children and adolescents of 10–20 years, and is considered as the second cause of death in this age group (Shabani et al, ). Epidemiological studies show that in the United States (US), 4–5 children per million annually suffer from the disease.…”
Section: Osteosarcomamentioning
confidence: 99%